2008
DOI: 10.1097/mph.0b013e31815cc3eb
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Percent Body Fat Indicators in Pediatric Oncology Nutrition Assessment

Abstract: Simple anthropometric measurements of %IBW and triceps skinfolds are good indicators of percent body fat and should be incorporated into regular nutrition assessment of the pediatric oncology patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 26 publications
1
22
1
8
Order By: Relevance
“…The HSCT procedures in this study were This study defines overweight by anthropometric measures, not by body composition measures; however, a strong correlation has been found between percent body fat and %IBW in the pediatric oncology population. 23 Future studies are suggested to examine the effect of body composition on survival in cancer patients, as it may be a low level of body cell mass (BCM) in the overweight patients that is leading to the poor survival. Previous studies have shown that pediatric cancer patients may have high fat mass but low BCM.…”
Section: Discussionmentioning
confidence: 99%
“…The HSCT procedures in this study were This study defines overweight by anthropometric measures, not by body composition measures; however, a strong correlation has been found between percent body fat and %IBW in the pediatric oncology population. 23 Future studies are suggested to examine the effect of body composition on survival in cancer patients, as it may be a low level of body cell mass (BCM) in the overweight patients that is leading to the poor survival. Previous studies have shown that pediatric cancer patients may have high fat mass but low BCM.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric measurements, including middle upper arm circumference, triceps, biceps, suprailiac and subscapular skinfolds and arm muscle mass, are preferred indicators of body composition in oncology patients [1,3]. Midarm circumference and triceps and biceps skinfolds have been reported to be more accurate indicators of malnutrition at diagnosis than weight and height indices [3]. Early indication for enteral nutrition therapy is one of the main goals of nutritional therapy in children and adolescents with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The most sensitive indices for growth in children include weight, height for age and body mass index (BMI) [5]. Anthropometric measurements, including middle upper arm circumference, triceps, biceps, suprailiac and subscapular skinfolds and arm muscle mass, are preferred indicators of body composition in oncology patients [1,3]. Midarm circumference and triceps and biceps skinfolds have been reported to be more accurate indicators of malnutrition at diagnosis than weight and height indices [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations